Marathon Running Transiently Causes Medial Meniscus Extrusion: Recovery Time Course and Factors Associated With Extrusion - Shinya Dobashi; Koji Iwasaki; Shunto Tanaka; Ryosuke Hishimura; Masatake Matsuoka; Taku Ebata; Dai Sato; Tomohiro Onodera; Eiji Kondo; Norimasa Iwasaki (Scandinavian Journal of Medicine & Science in Sports, 2026)
ABSTRACT Meniscal recovery time following marathon running remains unknown, despite the need for practical recommendations on post‐race return to training. We aimed (1) to characterize the time course of medial meniscus extrusion (MME) after a full marathon and (2) to identify baseline factors associated with the magnitude of the acute increase in MME. One hundred recreational runners (200 knees; mean age 47.2 years; 77 men, 23 women) from five marathons underwent weight‐bearing, fully extended‐knee portable ultrasonography at baseline and immediately post‐race, and 90 runners (180 knees) were reassessed on post‐race Days 1–5. Meniscus extrusion was measured as the distance from the medial tibial plateau to the outer meniscal edge. Baseline medial‐to‐lateral load distribution was quantified as walking knee adduction moment (KAM) impulse from a tibia‐mounted inertial measurement unit, normalized to body mass and height. Linear mixed‐effects models evaluated associations between acute extrusion change and candidate predictors. Mean baseline MME was 1.14 mm (95% CI 1.06–1.22) and increased to 1.57 mm (1.49–1.66) immediately post‐race, a 38% increase (mean ΔMME 0.44 mm, 0.41–0.47; p < 0.001). MME remained significantly elevated through Day 3 ( p < 0.01) but returned to baseline from Day 4 onward ( p > 0.05). In multivariable analysis, a greater acute increase was independently associated with higher normalized KAM impulse ( β = 0.24, 95% CI 0.10–0.37), higher BMI ( β = 0.22, 0.09–0.36), and higher monthly running distance ( β = 0.18, 0.04–0.31), with a borderline association for age ( β = 0.15, −0.00 to 0.31). MME increased transiently after a marathon and returned to pre‐race levels by approximately Day 4; whether this transient change has clinical consequences, or warrants a specific recovery interval, requires further study.